P2Y6 Receptor Activation Promotes Inflammation and Tissue Remodeling in Pulmonary Fibrosis - Müller, Tobias; Fay, Susanne; Vieira, Rodolfo Paula; Karmouty-Quintana, Harry; Cicko, Sanja; Ayata, Cemil Korcan; Zissel, Gernot; Goldmann, Torsten; Lungarella, Giuseppe; Ferrari, Davide; Di Virgilio, Francesco; Robaye, Bernard; et al. (Frontiers in Immunology, 2017)
Idiopathic pulmonary fibrosis (IPF) is a disease with a poor prognosis and very few available treatment options. The involvement of the purinergic receptor subtypes P2Y2 and P2X7 in fibrotic lung disease has been demonstrated recently. In this study we investigated the role of P2Y6 receptors in the pathogenesis of IPF in humans and in the animal model of bleomycin-induced lung injury. P2Y6R expression was up-regulated in lung structural cells but not in broncho-alveolar lavage (BAL) cells derived from IPF patients as well as in animals following bleomycin administration. Furthermore, BAL fluid levels of the P2Y6R agonist uridine-5’-diphosphate (UDP) were elevated in animals with bleomycin-induced pulmonary fibrosis. Inflammation and fibrosis following bleomycin administration were reduced in P2Y6R-deficient compared to wild type animals confirming the pathophysiological relevance of P2Y6R subtypes for fibrotic lung diseases. Experiments with bone marrow chimeras revealed the importance of P2Y6R expression on lung structural cells for pulmonary inflammation and fibrosis. Similar effects were obtained when animals were treated with the P2Y6R antagonist MRS2578. In vitro studies demonstrated that proliferation and secretion of the pro-inflammatory / pro-fibrotic cytokine IL-6 by lung fibroblasts are P2Y6R-mediated processes. In summary, our results clearly demonstrate the involvement of P2Y6R subtypes in the pathogenesis of pulmonary fibrosis. Thus, blocking pulmonary P2Y6 receptors might be a new target for the treatment of IPF.